Preservation of Glial Cytoarchitecture from Ex Vivo Human Tumor and Non-Tumor Cerebral Cortical Explants: A Human Model to Study Neurological Diseases - Chaichana, Kaisorn (2007)
For the human brain, in vitro models that accurately represent what occurs in vivo are lacking. Organotypic models may be the closest parallel to human brain tissue outside of a live patient. However, this model has been limited primarily to rodent-derived tissue. We present an organotypic model to maintain intraoperatively collected human tumor and non-tumor explants ex vivo for a prolonged period of time (∼ 11 days) without any significant changes to the tissue cytoarchitecture as evidenced through immunohistochemistry and electron microscopy analyses. The ability to establish and reliably predict the cytoarchitectural changes that occur with time in an organotypic model of tumor and non-tumor human brain tissue has several potential applications including the study of cell migration on actual tissue matrix, drug toxicity on neural tissue, and pharmacological treatment for brain cancers, among others.